Republic of Slovenia : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Information Annex highlights that Slovenia maintains an exchange system that is free of restrictions on the making of payments and transfers for current international transactions, with the exception of exchange restrictions maintained for security reasons. Slovenian fiscal statistics are timely and high quality. The Ministry of Finance publishes a comprehensive monthly Bulletin of Government Finance, which presents monthly data on the operations of the state budget, local governments, social security, and the consolidated general government. The coverage of general government excludes the operations of extrabudgetary funds and general government agencies' own revenues. However, these operations are small.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet